Réponses

2013-05-01T16:29:36+02:00

9x² +6x + 1 = (3x+1)²

 

x² -14x+49  = (x -7)²

 

1+12x+36x² = (6x +1)²

 

x²-64  = (x -8 )(x+8)                                       49x²-4 =  (7x -2)(7x +2)

 

81-x²    = (9-x)(9+x)                                       1-16x² = 

 

25x²-36 = (5x-6)(5x+6)                                 4x²-9 = (2x-3)(2x+3)

 

2013-05-01T16:39:34+02:00

9x² + 6x + 1 = (3x + 1)²

on utilise (a + b)²

 

x² - 14x + 49 = (x - 7)²

on utilise (a - b)²

 

1 + 12x + 36x² = (6x + 1)²

on utilise (a + b)²

  x² - 64 = (x - 8)(x + 8) on utilise (a - b)(a + b)   81 - x² = (9 - x)(9 + x) on utilise (a - b)(a + b)   25x² - 36 = (5x - 6)(5x + 6) on utilise (a - b)(a + b)   49x² - 4 = (7x - 2)(7x + 2) on utilise (a - b)(a + b)   1 - 16x² = (1 - 8x)(1 + 8x) on utilise (a - b)(a + b)   4x² - 9 = (4x - 9)(4x + 9) on utilise (a - b)(a + b)